Medea Euripides between text and contemporary theatrical presentation (Al-Academy, 2024)
It is not available for us to go back in time and see plays old and it plays giants tragedy ancient Greek (Aeschylus, Sofokls, and yourbedes) through the eyes of a generation ago, and if we were able to go back to Ntegathm play it is certain that we will not taste or Nstassig for much of what we see from these offers will not afford the traditional religious rituals, which was accompanied also dance and music in the style of ancient Greek play was representing a large part of the theater see manifestations Can our eyes and ears we twentieth century audience to accept those appearances, and it was then?Inevitably it will look like a museum bycollection not only. So we find ourselves in the light of the foregoing forced When you do remove it that werenew and wewear dress contemporary without limit ourselves to re-display alone, taking into consideration a bridge between past and present to build this bridge by creating a unit harmony between the theatrical old as it was in its time and it must be in our time approaching taste Mtafrjna the contemporary The essence of this association can achieve the following:- The goal of the author. Any content and ideas that envisaged broadcast to the public.- Appropriate theater to the taste of the contemporary theater audience.Perhaps one of the a priori what humility him interested and scholars to bring theater to be on top of what operating theater director that hurt his excretory in the service of the text of theater and its audience, as it is not plays prototype is Square Stadium reviewing the talents of the director, has no right to change the meaning or philosophy matched or a sense of meaning, but what permitted him play and meaning.And according to this vision, the director d. Adel Karim provide a range plays heritage of ancient Greek without being sidetracked in his directorial contemporary purpose and philosophy of the play, but tried hard to maintain a secretary's speech Author drama, and documents the link between the text as it was (except for some of the measures which he found necessary to promote and achieve his experience) and between a bystander local taste. Introduced some of the plays poet, playwright Sofokls (Antekohna, Electra, Oedipus king) and some another was awarded to playwright Iorbidha who was representing the third side of the triangle tragic Greek (Aeschylus, Sofokls, and yourbedes) selected him play (Media) and highlighting them in his research that model of an applied for this type of plays Greek submitted by seeing getmeout contemporary and forward-looking to the reality of welcome and Piazza put more comprehensive issues of modern man, what carries this play (which represents a model of models of theatrical social) ability to openness towards one of the problems of our time so that the events and attitudes that passed out (Media - Women) Greek, is what can be faced by women in our current way or another, where the content of the play reveals the point of consider ethical yourbedes and position of the misery of the social status of Greek women in the ancient Greek era